The spillover effects of financial misconduct on the value of cash of peer firms. Issue 4 (4th February 2022) - Palkar, Darshana D.
Abstract : Purpose: Prior research has documented a guilt by association phenomenon whereby instances of corporate misconduct generate a negative spillover to innocent firms due to their shared industry membership with the wrongdoing firm. However, research on competitive dynamics predicts a positive spillover whereby some firms benefit from the revelation of financial misconduct by an industry peer. This study lends support to both these effects by highlighting the role product similarity plays in the understanding of investors' perceptions surrounding corporate misconduct. Design/methodology/approach: The study assesses the investors' valuation of cash using Faulkender and Wang's (2006) methodology. The difference-in-differences approach is employed to compare the market valuation of cash held by non-accused firms with higher and lower litigation spillover risk operating in industries with higher vs lower product similarity. Findings: The findings show that an increase in the volume and severity of misconduct by industry peers is associated with an undeserved loss in the value of cash held by non-accused firms operating in industries with high product similarity. In contrast, firms that sell differentiated products stand to gain from the troubles of the accused peer. Moreover, non-accused firms in industries with high product similarity reduce capital expenditures more following misconduct accusations against peers to preserve cash in anticipation of future lawsuits. Originality/value: This study contributes to the growing spillover literature that investigates how a crisis caused by one firm affects the valuation of its peers.